Schedule overruns as a barrier for liquefied natural gas projects: A review of the literature and research agenda - Munmun Basak; Robert K. Perrons; Vaughan Coffey (Energy Reports, 2019)
With only half of the carbon footprint of coal, natural gas is widely considered to be an important transition fuel as the world economy shifts away from more carbon-intensive energy sources towards lower-carbon alternatives. Liquefied natural gas (LNG) has accordingly grown as a solution for connecting producers and consumers of this valuable resource that are geographically separated by large distances or barriers that make pipelines infeasible. Many construction projects are underway or being planned around the world to bring onstream the vast amounts of infrastructure required for this strategically important energy source. Despite the importance of these projects, however, they are frequently plagued by significant overruns in both scheduling and cost that could impede the progress of the adoption of natural gas in both the short- and long-term. Towards understanding these impediments, this paper puts forward a systematic literature review that synthesizes project management research and prior contributions in the LNG domain to identify risk factors that are most important to schedule and cost overruns in LNG projects. We then put forward a series of research questions that highlight the most fruitful areas for future investigations in this area, thereby helping to lay the groundwork for research that would potentially speed up the rate at which new natural gas supplies can supplant more carbon-intensive fuel sources around the world.
Keywords: 330; Liquefied natural gas; LNG; Risk factors; Schedule overruns; Upstream